Edible and Functionalized Films/Coatings—Performances and Perspectives - Sorin Marius Avramescu (Coatings, 2020)
In recent years, food packaging has evolved from an inert and polluting waste that remains after using the product toward an active item that can be consumed along with the food it contains. Edible films and coatings represent a healthy alternative to classic food packaging. Therefore, a significant number of studies have focused on the development of biodegradable enveloping materials based on biopolymers. Animal and vegetal proteins, starch, and chitosan from different sources have been used to prepare adequate packaging for perishable food. Moreover, these edible layers have the ability to carry different active substances such as essential oils—plant extracts containing polyphenols—which bring them considerable antioxidant and antimicrobial activity. This review presents the latest updates on the use of edible films/coatings with different compositions with a focus on natural compounds from plants, and it also includes an assessment of their mechanical and physicochemical features. The plant compounds are essential in many cases for considerable improvement of the organoleptic qualities of embedded food, since they protect the food from different aggressive pathogens. Moreover, some of these useful compounds can be extracted from waste such as pomace, peels etc., which contributes to the sustainable development of this industry.